Immune response variations and intestinal flora changes in mastitis induced by three Streptococcus uberis strains. (3rd January 2022) - Fu, Shaodong; Zhou, Yuanyuan; Qiu, Yawei; Chen, Wei; Zhang, Jinqiu; Miao, Jinfeng
Abstract: Streptococcus uberis is a common cause of mastitis. The pathogenicity among different strains of S. uberis and the resultant host immune responses remain to be elucidated. Herein, we document immune responses among three strains of S. uberis, and preliminary explore whether and how intestinal immunity plays a role in host anti‐infection processes. Mice have been proved to be effective experimental animals for bovine mastitis, so utilizing a mouse intramammary infection model, we assay immune responses and gut flora changes of three S. uberis strains by histopathologic examination, RT‐PCR, Western blot, and 16s ribosomal DNA sequencing. We find that the immune responses among the three sequence‐type (ST) S. uberis strains may be linked to the hasA/B and lbp virulence genes, and the beta diversity of the intestine may be independent of the ST of S. uberis . Twenty phyla and 30 genera of intestinal flora were identified, with Verrucomicrobia and Akkermansia being the most prominent phylum and genus, respectively. These bacteria have strong anti‐inflammatory and protective effects against S. uberis challenge. These data provide a foundation for further studies to elucidate gut flora function and exploration of therapeutic targets for mastitis.